2015
DOI: 10.1007/s11746-015-2592-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Transesterified Palm Olein‐Based Polyol and Rigid Polyurethanes from this Polyol

Abstract: Transesterification of palm olein with glycerol can increase the functionality by introducing additional hydroxyl groups to the triglyceride structure, an advantage compared to using palm olein directly as feedstock for producing palm-based polyol. The objective of this study was to synthesize transesterified palm olein-based polyol via a three-step reaction: (1) transesterification of palm olein, (2) epoxidation and (3) epoxide ring opening. Transesterification of palm olein yielded approximately 78 % monogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 9 publications
2
50
0
2
Order By: Relevance
“…However, many of them require the use of rare and/or expensive catalysts, sometimes additional costs are required for the isolation and purification of the final product. The most effective and simple method is using performic acid as an epoxidizing reagent, which is formed in situ from hydrogen peroxide and formic acid (Arniza et al, ; Doll and Erhan, ; Lee et al, ; Saurabh et al, ; Tuan et al, ). However, the optimization of epoxidation conditions is a necessary procedure due to the different fatty‐acid composition of vegetable oils.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of them require the use of rare and/or expensive catalysts, sometimes additional costs are required for the isolation and purification of the final product. The most effective and simple method is using performic acid as an epoxidizing reagent, which is formed in situ from hydrogen peroxide and formic acid (Arniza et al, ; Doll and Erhan, ; Lee et al, ; Saurabh et al, ; Tuan et al, ). However, the optimization of epoxidation conditions is a necessary procedure due to the different fatty‐acid composition of vegetable oils.…”
Section: Resultsmentioning
confidence: 99%
“…Di dunia industri, poliuretan diproduksi dalam bentuk busa-busa yang kuat dan fleksibel dengan konduktivitas rendah sehingga dapat digunakan sebagai bahan isolator panas (Stevens, 2007 Arniza et al (2015) juga telah melakukan sintesis poliuretan dari poliol hasil transesterifikasi minyak kelapa sawit. Berdasarkan uraian di atas penambahan aditif pada proses polimerisasi sebagai pemanjang rantai (chain extender) diperlukan agar lebih mudah bereaksi dengan isosianat dan diperoleh busa poliuretan dengan sifat termal yang lebih baik.…”
Section: Pendahuluanunclassified
“…Not only restricted for food purposes, high oleic oils have been utilized for non-food applications. Vegetable-based high oleic oil can be further processed via transesterification to produce products such as polyurethane [8]. Ramli et al [9] indicated that palm oil is among the vegetable source of monounsaturated fatty acids due to the abundant amount of palm oil available in Malaysia as compared to soybean and sunflower oils.…”
Section: Introductionmentioning
confidence: 99%